Evaluation of a double-setting alpha-tricalcium phosphate cement in eviscerated rabbit eyes - Oria, A. P.; Neto, FAD; Laus, J. L.; dos Santos, L. A.; Piza, E. T.; Brunelli, A. T.; Nishimori, C. T.; de Souza, ALG (Lippincott Williams & Wilkins, 2006)
Purpose: To evaluate the macroscopy, microstructure, and tissue reaction of a double-setting a-tricalcium phosphate bone cement used as an intraocular implant in rabbits.Methods: the internal and external surface of the double-setting a-tricalcium phosphate implant was analyzed macroscopically and by scanning electron microscopy. Twelve New Zealand rabbits received 12-mm implants made of double-setting alpha-tricalcium phosphate cement after unilateral evisceration. Clinical evaluation was performed daily for the first 15 days after surgery and at 15-day intervals until the end of the study period. For histopathologic analysis, 3 animals per experimental period were submitted to enucleation at 15, 45, 90, and 180 days.Results: on gross inspection, the external surface of the implant was solid, smooth, and compact. The microarchitecture was characterized by the formation of columns of hexagonal crystals with interconnecting channels forming micropores. No wound dehiscence, signs of infection, or implant extrusion were observed in any animal throughout the study period. Histologic examination revealed the formation of fibrovascular tissue surrounding the implants, and there were signs of minimal integration of the surface limiting the fibrocellular cap with the space previously occupied by the implant.Conclusions: the double-setting alpha-tricalcium phosphate implant behaved as an inert and nonintegratable material. The lack of incorporation of this material by fibrovascular tissue is related to its characteristics of compactness and high resistance.